The Atopic March. A Literature Review - Juan F. Salazar-Espinosa (University Library System, University of Pittsburgh, 2014)
The atopic march is defined as the progression of atopic diseases, generally during childhood, such as atopic dermatitis, asthma, allergic rhinitis and food allergies. The main risk factors for developing these atopic diseases include genetics, aeroallergens, food allergens, latefood introduction to the infant, and living in developing countries. The immunologic contributors to this problem include the Th2 response, epigenetics, and lack of certain factors like thymic stromal lymphopoietin (TSLP) and filaggrin. As a whole, the therapeutic approach has been changing during recent years because of the discovery of new factors involved in this problem. This article explains the definition of atopic march, the immunological pathway, clinical features, epidemiology and therapeutic approaches to create a context for the broader understanding of this important condition.